Stage-specific fecal and salivary microbiota signatures for noninvasive detection of colorectal cancer - Wu, Zhenzhen; Zhu, Zhenzheng; Zhou, Chenxi; Lin, Zhenyi; Yang, Hujia; Jiang, Guanjun; Ding, Shuning; Yu, Jieru; Sun, Leitao (Frontiers in Microbiology, 2025)
BackgroundFecal and salivary microbiota dysbiosis play a crucial role in the pathogenesis of colorectal cancer (CRC). We investigated whether the fecal and salivary microbiota were altered during colorectal tumorigenesis and evaluated their diagnostic performance.MethodsWe enrolled 30 metastatic CRC patients, 30 nonmetastatic CRC patients, and 30 healthy controls between October 2023 and September 2024. Fecal and salivary samples were collected for microbial profiling via 16S rDNA sequencing and bioinformatics analysis.ResultsFecal and salivary microbiota composition differed during CRC progression, with salivary microbiota progressively enriched in the gut. In addition, fecal and salivary microbial co-occurrence networks dynamically altered during CRC progression. The natural connectivity of fecal microbial community networks exhibited decreased stability, whereas salivary microbial community networks showed increased stability as CRC progressed. Finally, specific fecal microbial amplicon sequence variants (ASVs) associated with colorectal carcinogenesis enabled precise stage-specific diagnosis of CRC, outperforming salivary ASVs classifiers.ConclusionThis study elucidates stage-specific microbial dynamics in CRC, providing novel insights into clinical diagnostic strategies.